Association of CTRC and SPINK1 gene variants with recurrent hospitalizations for pancreatitis or acute abdominal pain in lipoprotein lipase deficiency - Tremblay, Karine; Dubois-Bouchard, Camélia; Brisson, Diane; Gaudet, Daniel (Frontiers in Genetics, 2014)
Background: There are important inter-individual variations in the incidence and severity of acute pancreatitis in patients with severe hypertriglyceridemia. Several genes involved in triglyceride-rich lipoprotein metabolism or serine proteases pathways are known to influence the risk of pancreatitis. Aim: To evaluate the association between genes regulating serine proteases, chymotrypsin C (CTRC) and serine peptidase inhibitor kazal type1 (SPINK1), and recurrence of hospitalizations for acute pancreatitis or severe abdominal pain in patients with Lipoprotein Lipase deficiency (LPLD), a rare and extreme monogenic model of severe hypertriglyceridemia and pancreatitis. Method: The CTRC and SPINK1 genes promoter and coding regions sequencing has been performed in a sample of 38 LPLD adults (22 men and 16 women) and 100 controls (53 men and 47 women). Estimation of the association of CTRC and SPINK1 gene variants or combinations of variants with history of hospitalizations for pancreatitis or acute abdominal pain in LPLD was investigated using non parametric analyses with correction for multiple testing and logistic regression models controlling for age, gender, family history and life habits. Results: Gene sequencing followed by genotype-stratified analyses of the CTRC and SPINK1 genes in LPLD and controls revealed a positive association between recurrence of hospitalizations and the rs545634 (CTRC) - rs11319 (SPINK1) combination (OR = 41.4 [CI: 2.0-848.0]; p=0.016). In all models, a positive family history of pancreatitis was a significant predictor of recurrent hospitalizations independently of the contribution of SPINK1 or CTRC (p< 0.001). Conclusion: These results suggest that a positive family history of pancreatitis and genetic markers in the serine protease pathways could be associated with a risk of recurrent hospitalization for acute pancreatitis in severe hypertriglyceridemia due to LPLD.